The internet as a labor market matchmaker - Peter Kuhn (IZA World of Labor, 2014)
Since the internet's earliest days, firms and workers have used various online methods to advertise and find jobs. Until recently there has been little evidence that any internet-based tool has had a measurable effect on job search or recruitment outcomes. However, recent studies, and the growing use of social networking as a business tool, suggest workers and firms are at last developing ways to use the internet as an effective matchmaking tool.
Keywords: J64; 330; job search; recruitment; internet; matching; job boards